Gauging the effects of the German COVID-19 fiscal stimulus package - Natascha Hinterlang; Stéphane Moyen; Oke Röhe; Nikolai Stähler (Deutsche Bundesbank, 2021)
We simulate the fiscal stimulus packages set up by the German government to allevi-ate the costs of the COVID-19 pandemic in a dynamic New Keynesian multi-sectorgeneral equilibrium model. We find that, cumulated over 2020-2022, output lossesrelative to steady state can be reduced by more than 4 PP. On average, welfare costsof the pandemic can be mitigated by 5%, and even by 20% for liquidity-constrainedhouseholds. The long-run present value multiplier of the package amounts to 0.2. Consumption tax cuts and transfers to households primarily stabilize private con-sumption, and subsidies prevent firm defaults. The most cost-efficient measure isan increase in productivity-enhancing public investment. However, it materializesonly in the medium to long-term.
Keywords: E1; E2; E62; H2; H30; 330; Fiscal Policy; COVID-19; DSGE Modelling; Sectoral Heterogeneity